The Study on the Constitutive Model of Concrete for Explicit Dynamic of ABAQUS Based on Damage Energy. (23rd September 2022) - Chen, Lihao; Liu, Dewen; Lei, Min; Zhang, Yuan; Zhao, Tiange; Zheng, Yanping
Abstract : In this paper, the elastoplastic damage constitutive model of concrete is established based on the damage energy release rate to analyze the failure of concrete structures. Based on the user-defined material program VUMAT interface provided by the ABAQUS, the explicit algorithm is used to secondary develop the concrete model. The model is verified from mechanical behavior, mesh-dependence, and stress state under reciprocating loading. The results show that the model can reasonably simulate the mechanical state of concrete under compression and tension and can effectively solve the mesh-dependence problem in finite element problems. The simulation results were still consistent when the mesh size was 2.5 mm. The low cycle reciprocating simulation test of the concrete column also proves that the model has better hysteretic and bidirectional coupling performance. It is verified that the VUMAT material subroutine can meet the analysis requirements of reinforced concrete structures and can be used to simulate the dynamic response of structures with strong nonlinear stages.